2019
DOI: 10.1111/asj.13261
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hypothalamic genes in associating with food intake during incubation behavior in domestic chicken

Abstract: The molecular mechanism underlying in the onset and maintenance of incubation behavior are not fully understood, and it is still unknown the reason why White Leghorn, a layer strain, hens never display incubation behavior. Therefore, to explore specific hypothalamic genes regulating incubation behavior, cap analysis of gene expression (CAGE) were applied to comparison between incubating Silkie and laying White Leghorn hens. In addition, mRNA expression of some differentially expressed genes (DEGs) and melanoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In the presence of elevated insulin concentrations, POMC and CART expression has been reported to elevate, while the expression of NPY is inhibited ( Porte et al, 2002 ; Honda et al, 2007 ; Shiraishi et al, 2008 ). This is of particular interest as POMC has been found to increase in incubating Silkie hens, a period known to be associated with high PRL levels, compared to their laying counterparts ( Sharp et al, 1989 ; Dawson, 2008 ; Takeda and Ohkubo, 2019 ). As AdipoR1 is upregulated in the presence of PRL, it would be expected that adiponectin levels would elevate during this period, yet concentrations have been observed to decline through to the end of production in turkey hens ( Diot et al, 2015 ), requiring further investigation to determine its role throughout a production cycle.…”
Section: Impact Of Body Weight and Composition On The Hpg-axismentioning
confidence: 99%
“…In the presence of elevated insulin concentrations, POMC and CART expression has been reported to elevate, while the expression of NPY is inhibited ( Porte et al, 2002 ; Honda et al, 2007 ; Shiraishi et al, 2008 ). This is of particular interest as POMC has been found to increase in incubating Silkie hens, a period known to be associated with high PRL levels, compared to their laying counterparts ( Sharp et al, 1989 ; Dawson, 2008 ; Takeda and Ohkubo, 2019 ). As AdipoR1 is upregulated in the presence of PRL, it would be expected that adiponectin levels would elevate during this period, yet concentrations have been observed to decline through to the end of production in turkey hens ( Diot et al, 2015 ), requiring further investigation to determine its role throughout a production cycle.…”
Section: Impact Of Body Weight and Composition On The Hpg-axismentioning
confidence: 99%
“…In avians, the analysis of mRNA expression pattern showed that POMC was mainly expressed in the pituitary, brain, hypothalamus ( Gerets et al, 2000 ; Liu et al, 2020 ). Hypothalamic POMC is identified to be associated with food intake in chickens ( Takeda and Ohkubo, 2019 ). Increasing evidence has indicated the important role of POMC in regulating the avian reproduction, including incubation behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, increased POMC in hypothalamus can cause appetite reduction of incubating avians, which is considered to be a prerequisite to initiate incubation. Transcriptome analysis further revealed that POMC seemingly occupied a key position in the regulatory network of incubating avian hypothalamus ( Liu et al, 2018 ; Takeda and Ohkubo, 2019 ). Consistently, POMC were observed to increase in incubating Changshun hens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation